Respon Pertumbuhan Ayam Lokal Pedaging terhadap Suplementasi Protein Isolasi Biji-bijian (PIB) dan Perbedaan Level Protein Ransum - M. Aman Yaman; Zulfan Zulfan; Andi Saputra (Agricultural Faculty, 2009)
The response of local meat chicken growth to supplementation of isolated grain protein and the difference in ration protein levelABSTRACT. A research which aims to determine the response of local meat chicken growth of protein supplementation with Isolation Grains Protein (IGB) and the difference in ration protein level has been conducted in the Laboratory of Experimental Farm, Animal Husbandry Department, Faculty of Agriculture, Syiah Kuala University-Darussalam, Banda Aceh for 90 days. This study used a completely randomized design factorial with 2 factors, consisting of factors namely male gender (JJ) and female (JB) and the ration is a combination of factors and levels IGB in the ration, ie: treatment A: 17% protein and 0.4% IGB; treatment B 19% protein and 0.6% IGB and treatment C 21% protein and 0.8% IGB. Each combination consisted of 4 replications and each replication consists of 5 chickens. Parameters observed in the study were weight gain, achievement of final weight, consumption, conversion and efficiency of ration. DOC used a derivative result of selection of local meat chicken which are in the process of selection. Data acquired and processed by ANOVA.The results showed that supplementation of IGB and ration protein level difference was significantly effect (P 0.01) on weight gain, final weight, rate of consumption, conversion efficiency of rations and rations, but there is no interaction effect between sex and ration factors . The highest weight gain obtained in the male local chicken achieved by feeding a ration B (93.23 grams), while the hen rations achieved by providing treatment C (63.86 grams / week). The highest final body weight of male chicken on treatment B (1491.5 gram/90 days) and hens in treatment C (1061.5 gram/90 days). However, the highest ration consumption in both male and female local chickens obtained from the ration A. Feed conversion value and the best feed efficiency obtained in treatment B for the treatment of male and C for female chicken. The study concluded that there were different responses between male and female local chickens of the use of IGB in the rations. In male local chicken, IGB is more effective when added in the ration with a protein level of 19% whereas in female at the protein level of 21%.